From Theory of Knowledge Management to Practice (IntechOpen, 2024)
From Theory of Knowledge Management to Practice is a collaborative compilation featuring contributions from various authors. The book amalgamates analytical principles with the practical aspects of knowledge management in the business realm. Its unique contribution lies in bridging the gap between engineering/technology disciplines and the organizational, administrative, and planning dimensions of knowledge management. This integration is particularly valuable when viewed in conjunction with other sub-disciplines like economics, finance, marketing, and decision and risk analysis, among others. The book not only introduces but also illustrates knowledge management theories through practical case studies. These case studies showcase significant outcomes across different sectors, drawing on diverse real-world scenarios. The theoretical framework is accompanied by relevant analytical techniques, adopting a progressive approach that transitions from basic concepts to intricate and dynamic decision-making processes involving multiple data points, including big data and extensive datasets. The integration of computational techniques, dynamic analysis, probabilistic methods, and mathematical optimization further enhances the book's utility, offering expert support for the analysis of multi-criteria decision-making problems characterized by specific constraints and requirements.